Peningkatan Kapasitas dalam Penyusunan Detail Engineering Design (DED) untuk Penataan Kawasan Permukiman di Kecamatan Gunungsari - Faizi, Syahrul; Rizal, Muammad (Journal of Community Development and Empowerment, 2025)
Residential area management is a strategic effort to improve the quality of life and support sustainable development. However, preparing an effective and efficient Detail Engineering Design (DED) requires adequate technical capacity. This study aims to enhance the capacity for preparing DEDs for residential area management in Gunungsari Subdistrict. The research uses a qualitative approach with data collection techniques including interviews, observations, and document studies. The results indicate that improving technical capacity through training and mentoring in DED preparation is crucial for enhancing design quality, budget efficiency, and development sustainability. Furthermore, collaboration among local governments, communities, and other stakeholders plays a vital role in the successful preparation of DEDs. This study is expected to contribute to better planning and implementation of residential area management in Gunungsari Subdistrict, emphasizing community engagement and data-driven planning principles.